Fatal flowers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Compounds found in chrysanthemum daisies have been successfully exploited commercially for many years as pyrethrin insecticides. Now researchers have found, high in the Andes, another plant which they hope will have the same potential. The delicate...